PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS III SD - Koko Josianna Br Sembiring; Antonius Remigius Abi; Reflina Sinaga; Patri Janson Silaban (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article is derived from the implementation of the influence of learning independence on students’ learning outcomes at the third-grade level of SDN 030398 Lae Rambong Silima Pungga-Pungga in Dairi in the academic year 2021/2022. The research method used was survey research with a quantitative method. The population of research involved all students of SDN 030398 Lae Rambong. The technique used by the researchers was random sampling with a number of 30 students at class III elementary school. The data collection tool used by the researchers was a questionnaire on learning independence, which was distributed to 30 students. Whilst, learning outcomes could be seen from the students' scores. To test the hypothesis, it was used t-test hypothesis. The results showed that learning independence (X) had an average value of 78.87 and learning outcomes (Y) had an average value of 70. The results of the correlation coefficient of the research were rxy = 0.738 with the results of t-test hypothesis testing tcount 5,782 > ttable 2,048 with a significant level α = 0.05. H0 was rejected and Ha was accepted, which meant that there was a significant influence between learning independence and the learning outcomes of third-grade students at Elementary School 030398 Lae Rambong.